Polyacrylamide gel as a substitute of estrous mucus for sperm penetration test - KUMAR, AJEET; SINGH, JAGIR; PANGAONKAR, G R (The Indian Journal of Animal Reproduction, 2023)
Bovine estrual mucus is used for sperm penetration studies. But, major constraints are variation in the quality of mucus giving inconsistent result. For batches of l, 2 and 3% polyacrylamide gel were prepared and examined for their-physical properties viz., transparency, spinnbarkeit, pH and visible gelification. Two percent PAG resembled bovine estrous mucus, while 1% had watery consistency and 3% was very thick. The average pH values for the three grades of PAG were around 8.6. It was concluded that 2% PAG being more alike to bovine estrual mucus, could be used for sperm penetration studies.